2010
DOI: 10.1186/1471-2431-10-47
|View full text |Cite
|
Sign up to set email alerts
|

Xanthogranulomatous Pyelonephritis in a male child with renal vein thrombus extending into the inferior vena cava: a Case Report

Abstract: BackgroundWe present a case of Xanthogranulomatous pyelonephritis (XGPN) in a male child with renal vein thrombus extending into the inferior vena cava. This is a rare presentation. XGPN is a rare type of renal infection characterised by granulomatous inflammation with giant cells and foamy histiocytes. The peak incidence is in the sixth to seventh decade with a female predominance. XGPN is rare in children.Case presentationAn 11 year old male child presented with a history of high grade fever and chills, righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…The exact aetiology of XGPN is unknown, but is generally accepted that the disease process is associated with long-term obstruction and infection 1 3 4 10 14–16. Other factors have also been implicated and include altered immune response and intrinsic disturbance of leucocyte function, alterations of lipid metabolism, lymphatic obstruction, malnutrition, arterial insufficiency and venous occlusion 4 10 16…”
Section: Discussionmentioning
confidence: 99%
“…The exact aetiology of XGPN is unknown, but is generally accepted that the disease process is associated with long-term obstruction and infection 1 3 4 10 14–16. Other factors have also been implicated and include altered immune response and intrinsic disturbance of leucocyte function, alterations of lipid metabolism, lymphatic obstruction, malnutrition, arterial insufficiency and venous occlusion 4 10 16…”
Section: Discussionmentioning
confidence: 99%
“…A case series by Quinn et al showed an incidence of 6/1,000 surgically proven chronic pyelonephritis. Case reports have associated it with renal vein thrombi [212]. It presents with anorexia, weight loss, fever, chills, and dull, persistent flank pain.…”
Section: Kawasaki Diseasementioning
confidence: 98%
“…XGPN is often called "the great imitator.'' 14,15 Laboratory results show a microcytic anemia, leukocytosis, thrombocytosis, and increased C-reactive protein. 1,14 In our series, white blood cells and C-reactive protein rates are increased in one case (8.3%).…”
Section: Discussionmentioning
confidence: 99%
“…5,[11][12][13] Two forms of XGPN have been described, a diffuse form and a pseudo-tumoural (or focal) form, which is less frequent (15.4%). 1,14,15 The lower pole of the kidney is the most common location of focal XGPN. In our series, 50% of these lesions involved the lower pole.…”
Section: Discussionmentioning
confidence: 99%